2016
DOI: 10.1159/000445311
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Profile of 10 Afflicted Egyptian Families with 17-β-HSD-3 Deficiency

Abstract: This study aimed at the detection of HSD17B3 gene mutations in Egyptian patients with suspected diagnosis of 46,XY DSD due to 17-β-HSD-3 deficiency and at evaluation of phenotype/genotype relationship of these mutations. The study was conducted on 11 patients of 10 families which were provisionally diagnosed to have 17-β-HSD-3 enzyme deficiency. Karyotyping, hormonal evaluation of testosterone, Δ4-androstenedione, and dihydrotestosterone, and sequencing analysis of the 11 exons of the HSD17B3 gene were done. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Similar to our findings, SRD5A2 variants were the second most frequently reported cause of 46,XY DSD in Indian populations (Nagaraja et al, 2019). We have found that 17β‐Hydroxysteroid dehydrogenases III (HSD17B3) deficiency is relatively common in our cohort with a different mutational profile compared with that observed in other populations (Hassan et al, 2016) (Table 3). In contrast, only five pathogenic variants were detected in the AR gene out of 28 patients with suspected androgen insensitivity.…”
Section: Discussionmentioning
confidence: 46%
“…Similar to our findings, SRD5A2 variants were the second most frequently reported cause of 46,XY DSD in Indian populations (Nagaraja et al, 2019). We have found that 17β‐Hydroxysteroid dehydrogenases III (HSD17B3) deficiency is relatively common in our cohort with a different mutational profile compared with that observed in other populations (Hassan et al, 2016) (Table 3). In contrast, only five pathogenic variants were detected in the AR gene out of 28 patients with suspected androgen insensitivity.…”
Section: Discussionmentioning
confidence: 46%
“…Sixty-eight articles reported one or more patients with HSD17B3 mutations ( Supplemental Table S1 ) [ 1 , 3 , 4 , 5 , 9 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
Section: Resultsmentioning
confidence: 99%